(3GdeNJUQ ef JGQjN GdHTQs - (3ESeGYjd Hf Ydj Hf eMehO Hf eMeO Hf YeQ Hf TGgfTGg Hf CjhH(B: (3Gdedc GdeDjO, UGMH MeGI,J (B732 (3g` s ((3eMeO Hf EHQGgje Hf eMeO GdTgjQ HGdHTJci s)
(3ChdgG (B:s
(3GdMeO ddg GdPi Mce Ydi GdCYeGQ HGdELGd CeG HYO (B: (3Efg SfM di Cf ChQO ai cJGHi gPG TjFkG ef GdJhGQjN GdbOjeI hGdESdGejI , jchf JPcQI JZffi Yf eQGLYI GdcJH GdeWhdI s
(3BNQgG (B:s
(3Ke QMdJ SfI (B715(3g` hgPG BNQ eG hLOJg ef GdJGQjN GdeHGQc s
(3HgG fXGe GdJYbjHIs
(3fSNI fajSIs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B319 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B2 - (3U (B282s
Keywords: (3GdJGQjNs